Investigação da Interferência de Mutações Sobre a Interação da IsPETase com Ligantes via Simulação por Dinâmica Molecular - MARCIO FERNANDES DA SILVA (2024)
One of the leading causes of environmental pollution is the stacking of synthetic polymers in nature. To deal with this problem, the use of bacteria that produces polymer-degrading enzymes (biological treatment) might be an alternative. The PETase produced by I. sakaiensis (IsPETase) we chose, possesses great affinity towards polyethylene terephthalate (PET) as its carbon source and it is active at ambient temperature. Aided by Molecular Dynamics (MD) simulation, we investigated how single mutations on its active site interfere in its interactions with ligands – specifically the docking process. Mutate Isoleucine 180 for a Valine (variant I) and for an Alanine (variant II) reduced how many residues interact with the ligand, as well as increased the protein-ligand distance – caused by the decrease in the hydrogen bond formation between the protein and the ligand. Gibbs free energy also decreased due to the mutations, indicating some affinity loss between protein and ligand analyzed, compromising complex maintenance.